Data for article: Microplastics in Arctic Waters of the Finnish Sámi Area - Soininen, Tuomo,University of Eastern Finland; Uurasjärvi, Emilia,University of Eastern Finland; Koistinen, Arto,University of Eastern Finland; Mustonen, Tero,Snowchange Cooperative; Hämäläinen, Lauri,Snowchange Cooperative; Huusari, Noora,Snowchange Cooperative; Feodoroff, Juha,Snowchange Cooperative; Moshnikoff, Jouko,Snowchange Cooperative; Feodoroff, Pauliina,Snowchange Cooperative (2023)
Description of the dataset: This dataset was created in 2021 and made open in 2023 Lapland_Sampling.xlsx contains all sampling dates and coordinates alongside with sample names, volumes, area descriptions and codes used to describe the sites in the article. Lapland_RawData.xlsx contains all the raw data for all the samples.This includes polymer types, particle sizes and an estimation ofparticle mass. Furthermore, the file contains a table with all the polymer types and their counts from allsamples. Data creation and processing: The raw data was created by measuring filtered water samples with FPA-FTIR . The spectral analysis was done with siMPle (Primpke et al. 2020,Applied Spectroscopy, 74, 1127-1138,https://doi.org/10.1177/0003702820917760).